The Effect Of Using The Project Based Learning Model On Entrepreneurial Learning On Student Entrepreneurial Interest - Sihombing, Iin Nur Indrayani (UNIVERSITAS PAKUAN, 2023)
College graduates are expected to go beyond just getting a job but opening up jobs for others. Thus, universities must be able to foster an interest in entrepreneurship through entrepreneurship learning. So this study aims to determine the influence of the project-based learning model on entrepreneurial learning on students' entrepreneurial interests. The method used in this study is a pre-experimental method with a quantitative approach and the design used in this study is an experiment with one group pretest and posttest design. The results showed that the use of the project base learning model made students more interested in participating in entrepreneurship learning, so that entrepreneurial learning activities could take place effectively. Even students can be more enthusiastic in expanding their horizons about entrepreneurship, so that the interest in entrepreneurship continues to increase. So it can be concluded that the project base learning model in entrepreneurship learning affects students' entrepreneurial interests.